Approaches to Urban Slums : A Multimedia Sourcebook on Adaptive and Proactive Strategies - Mehta, Barjor; Dastur, Arish (Washington, DC : World Bank, 2012)
Approaches to urban slums are a multimedia sourcebook that comprises 14 self-running audiovisual presentations and 18 video interviews. It is organized into four broad sections: adaptive approaches, proactive approaches, case profiles, and thematic interviews. The sourcebook itself, which contains more than nine viewing hours of content on CD-ROM, does not exist in printed format. This guide provides an overview of the structure and content of the CD as well as approximate running times for the various sections. Approaches to urban slums builds on an extensive body of knowledge accumulated over 35 years from a wide range of sources. The 14 self-running audiovisual presentations include photographs, illustrations, maps, graphic animations, and aerial imagery, along with voice-over narration. The sourcebook's multimedia format facilitates the presentation of a highly complex subject by adding an audiovisual and spatial dimension to the descriptive and analytical discussion. The 18 video interviews provide access to the knowledge and opinions of urban stakeholders and experts on specific issues, and from various development perspectives, including development organizations, governments, Non-governmental Organizations (NGOs), community organizations, academia, and professional urban consulting.